Removed versus unremoved vicryl sutures used for subcuticular skin closure - Elsharkawy, Suzan S.; Dawood, Waleed A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective was to compare the difference between removing vicryl suture thread after skin healing or burry the knots and leaving it to be absorbed in situ, after subcuticular skin closure of Pfannesteil incisions. Methods: Prospective, randomized controlled trial included 449 eligible participants were prospectively recruited between July 2016 and June 2017. All selected patients had a pfannenstial incision with subcuticular skin closure using 2-0 absorbable vicryl stiches (for primary caesarean section or extra peritoneal surgical approach to the prostate, bladder and distal ureters). The left side knot was buried under the skin edge and a knot in the midline and the right edge was made. After 10 days postoperative, the right half of the stitch thread and the two knots were removed, and the left half of the thread was left in situ. Patients were observed for any complication at time of stitch removal, after one month and after 6 months’ post-operative. Results: Wound infection rate, hypertrophic scars, keloids and skin itching were significantly higher in the un-removed wound sides while skin dehiscence was significantly higher in the removed wound sides. Conclusions: Leaving behind absorbable suture material after wound healing -when used in subcuticular pfannenstial skin closure- is associated with increased rates of wound infection, hypertrophic scars, itching and keloids, which of course overweight any known benefits of the technique.